A Functional Connectivity Study to Investigate the Role of the Right Anterior Insula in Modulating Emotional Dysfunction in Borderline Personality Disorder. Issue 1 (January 2022) - Sampedro, Frederic; Aracil-Bolaños, Ignacio; Carmona i Farrés, Cristina; Soler, Joaquim; Schmidt, Carlos; Elices, Matilde; Pomarol-Clotet, Edith; Salvador, Raymond; Vega, Daniel; Pascual, Juan C.
ABSTRACT: Objective: Previous imaging studies in patients with borderline personality disorder (BPD) have detected functional brain dysfunctions. Mindfulness training may improve the symptoms of BPD, although the neural mechanisms involved remain poorly understood. This study had several key aims: a) to investigate the role of right anterior insula (rAI) functional connectivity in modulating baseline emotional status in BPD, b) to compare differences in connectivity changes after mindfulness training versus interpersonal effectiveness intervention, and c) to explore the correlation between longitudinal changes in imaging data and clinical indicators. Methods: Thirty-eight patients with BPD underwent resting-state functional magnetic resonance imaging. Participants completed self-report clinical scales and participated in a dialectical-behavioral therapy (mindfulness versus interpersonal effectiveness modules). Changes in clinical and imaging variables were evaluated longitudinally after completion of the first 10-week sessions of psychotherapeutic intervention. Results: At baseline, the rAI was strongly connected with the other salience network nodes and anticorrelated with most core nodes of the default mode network ( p < .05, corrected). The functional connectivity of the rAI correlated with emotional dysregulation and deficits in mindfulness capacities ( p < .05, corrected). After completion of psychotherapeutic intervention, both groups (mindfulness and interpersonal effectiveness) showed divergent posttherapy functional connectivity changes, which were in turn associated with the clinical response. Conclusions: The functional connectivity of the rAI seems to play an important role in emotion dysregulation and deficits in mindfulness capacities in individuals with BPD. Psychotherapy seems to modulate this functional connectivity, leading to beneficial changes in clinical variables. Abstract : Supplemental digital content is available in the text.